2000
DOI: 10.1021/np990509b
|View full text |Cite
|
Sign up to set email alerts
|

New Variotin Analogues from Aspergillus viridi-nutans

Abstract: Besides the antifungal agents variotin (1), wasabidienone B(0) (4), and phomaligin A (5), two new but inactive metabolites, viriditin (2) and O-methylviriditin (3), were isolated from extracts of the culture filtrate of liquid cultures of a strain of Aspergillus viridi-nutans. In addition, wasabidienone B(1) (6) was isolated and characterized by spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Thus, 1 H and 13 C NMR data suggested that 13 is a cyclohexenone derivative. [19][20][21][22] HMBC correlations were observed from H3-13 (δH 1.81) to C-2 (δC 115.5), C-1 (δC 202.2), and C-3 (δ C 177.8), from H 3 -14 (δ H 1.32) to C-1 (δ C 202.2) and C-6 (δ C 83.0), from H 3 -12 (δ H 4.08) to C-3 (δ C 177.8) and from H3-15 (δH 3.82) to C-5 (δC 172.3), confirming the presence of a cyclohexenone ring in 13 (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, 1 H and 13 C NMR data suggested that 13 is a cyclohexenone derivative. [19][20][21][22] HMBC correlations were observed from H3-13 (δH 1.81) to C-2 (δC 115.5), C-1 (δC 202.2), and C-3 (δ C 177.8), from H 3 -14 (δ H 1.32) to C-1 (δ C 202.2) and C-6 (δ C 83.0), from H 3 -12 (δ H 4.08) to C-3 (δ C 177.8) and from H3-15 (δH 3.82) to C-5 (δC 172.3), confirming the presence of a cyclohexenone ring in 13 (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from being reported as being a potential mycotoxin, viriditoxin has also been reported to be a candidate for treatment of antibiotic resistant bacteria (Wang et al 2003). Among the known extrolites are the antifungal drug variotin (Takeuchi et al 1959, 1964, Suzuki et al 1990, Omolo et al 2000), and other drug candidates such as cornexistins (Nakajima et al 1991, Fields et al 1996), SCH 643432 (Hegde et al 2003) and a penicillin-like compound (Burton 1949). The sideramins ferrirubrin and fusigen (Diekmann 1967, Domsch et al 1980) and the organic acids 3-indole-acetic acid (Bakalinerov 1968, Voinova-Raikova et al 1969), citric acid (Loesecke 1945), ethyleneoxide-α, β-dicarboxylic acid (Sakaguchi et al 1939), (3Z,5E)-octa-3,5-diene -1,3,4-tricarboxylic acid 3,4-anhydride (Aldridge et al 1980) have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The Trichoderma species were cultured in various media as reported by Schneider [14] and Omolo [15]. The fungal test organisms were grown in yeast glucose malt (modified) agar medium while the bacterial test organisms were cultured in nutrient broth (Difco, USA) [14].…”
Section: Methodsmentioning
confidence: 99%